Sedentary Behaviors in Today's Youth: Approaches to the Prevention and Management of Childhood Obesity. Issue 11 (11th September 2018) - Barnett, Tracie A.; Kelly, Aaron S.; Young, Deborah Rohm; Perry, Cynthia K.; Pratt, Charlotte A.; Edwards, Nicholas M.; Rao, Goutham; Vos, Miriam B.
Abstract : This scientific statement is about sedentary behavior and its relationship to obesity and other cardiometabolic outcomes in youth. A deleterious effect of sedentary behavior on cardiometabolic health is most notable for screen-based behaviors and adiposity; however, this relation is less apparent for other cardiometabolic outcomes or when sedentary time is measured with objective movement counters or position monitors. Increasing trends of screen time are concerning; the portability of screen-based devices and abundant access to unlimited programming and online content may be leading to new patterns of consumption that are exposing youth to multiple pathways harmful to cardiometabolic health. This American Heart Association scientific statement provides an updated perspective on sedentary behaviors specific to modern youth and their impact on cardiometabolic health and obesity. As we reflect on implications for practice, research, and policy, what emerges is the importance of understanding the context in which sedentary behaviors occur. There is also a need to capture the nature of sedentary behavior more accurately, both quantitatively and qualitatively, especially with respect to recreational screen-based devices. Further evidence is required to better inform public health interventions and to establish detailed quantitative guidelines on specific sedentary behaviors in youth. In the meantime, we suggest that televisions and other recreational screen-based devices be removed from bedrooms and absent during meal times. Daily device-free social interactions and outdoor play should be encouraged. In addition, parents/guardians should be supported to devise and enforce appropriate screen time regulations and to model healthy screen-based behaviors.